Land use changes and their impact on properties of some soil series of Nagpur district of maharashtra - KHAMBALKAR, PRIYADARSHANI ARUN; K, SEN T; S, CHATTERJI; V, VENUGOPALAN M (The Indian Journal of Agricultural Sciences, 2014)
Six soil series of Nagpur district, Maharashtra were studied to detect land use changes, their causes over a period of nine years and impact on soil properties. Introduction and spread of soybean, irrigation availability through various sources facilitate double cropping in Manori, Kinhala, Takali, Palora and Bahadura series except Hatodi series having triple cropping (rice-wheat-rice or rice-rice-rice) with short duration rice verities and provide assured income to farmers and caused the land use changes. The soil morphological properties indicate few variation and showing reduced color value of Ap horizon in Manori series to 3 from 4 whereas in Kinhala and Takali series reduced to 2 from 3 and in Hatodi series sub-surface horizon transformed from brown to dark brown. Impact of land use change on bulk density (BD) of Manori, Kinhala and Takali series recorded slight changes over the earlier status (year 1999) whereas, Hatodi series recorded highest value for surface 1.87 Mg/m3 followed by subsurface 1.93 Mg/m3 (year 2008). The soil pH showed slight changes and increase in soil organic carbon (SOC) at surface and subsurface under all soil series except Hatodi series over initial status. Increase in cation exchange capacity (CEC), percent base saturation (BS %) and exchangeable bases such as Ca and Mg were recorded under all series with few exceptions. Soils of examined series were rich in available nutrients especially potassium and nitrogen while Hatodi series showed poor value of available potassium over other soil series. Strikingly, it is observed that fine nodules of calcium carbonate (CaCO3) at surface and subsurface soils of all pedons except Hatodi series, interestingly presence of CaCO3 in these soils except Bahadura series was not reported earlier.